Association between Pulpal-Periapical Pathology and Autoimmune Diseases: A Systematic Review - Julia Guerrero-Gironés (MDPI AG, 2021)
Several studies have linked apical periodontitis and systemic diseases. The aim of this study is to present a systematic review of the available literature investigating whether there is an association between pulpal-periapical pathology and autoimmune disease. The review was conducted following the PRISMA statement. A literature search was performed in five databases. Studies involving patients with pulpal-periapical pathology and autoimmune diseases were included in the review. Based on the PICO model, the research question aimed to assess whether there is an increased risk of developing pulpal-periapical pathology in patients with autoimmune disease. Article selection, data extraction, and quality assessment were performed using an adapted version of the STROBE guidelines. A total of seven studies were included in our review. The types of articles were five case-control and two cross-sectional studies. Periapical pathologies were associated to three autoimmune diseases (diabetes mellitus I, rheumatoid arthritis, and inflammatory bowel disease). Among the included studies, four show a low risk of bias, while three present a moderate risk. There could be an association between apical periodontitis and autoimmune diseases, although most studies report statistically non-significant associations.